Mapping the Threat of Misuse of Blockchain Domain Name System (BDNS) Technology in Online Gambling in Indonesia: Analysis Using a Scenario Matrix Approach - Pridana, Hilman (Security Intelligence Terrorism Journal (SITJ), 2025)
Web3 technology echoes the paradigm of a secure, transparent, and privacy-preserving decentralized internet. Unfortunately, this digital transformation has opened up new opportunities for cybercriminals, for example online gambling bookies can utilize the Blockchain Domain Name System (BDNS) running on Web3 as a way to avoid tracking and blocking. This analysis aims to map the potential threats from misuse of BDNS technology through a two-dimensional scenario matrix approach using two main types of variables: (1) Native Web3 integration into popular browsers, and (2) Level of BDNS adoption by online gambling sites. The four scenarios produced will describe various levels of risk that require different mitigation strategies, in certain combination conditions will create the highest threat conditions where the conventional domain name blocking system is no longer effective in blocking online gambling sites. The results of this study are expected to identify weak signals from the evolution of online gambling threats, as well as become a basis for government agencies or policy makers in preparing anticipatory steps in dealing with the dynamics of digital threats in the Web3 era.